Optimization of Zakat Management by Bkm Masjid in Medan City Perspective of Law No.23 Of 2011 - Halim, Abdul; Pagar, Pagar; Tanjung, Dhiauddin (Faculty of Law, Universitas Pekalongan, 2024)
Law No. 38 of 1999, later amended by Law No. 23 of 2011 on the Administration of Zakat, provides the legal basis for the administration of zakat in Indonesia. These laws and regulations recognise only two entities, namely the National Zakat Amil Agency (BAZNAS) and the Zakat Amil Institution (LAZ), as the legal managers of zakat in Indonesia. In Medan, there are two types of amil zakat, as well as community-formed amil-amil zakat who manage zakat at the mosque level, specifically for zakat fitrah. It is important to note that some of these mosque-level Amils have been approved by the state through a sub-unit framework known as the Zakat Collection Unit (UPZ). Meanwhile, some of these amil-amil have not yet been approved by the state and are only based on the policies of the Prosperity Board (BKM) of each mosque. In Islamic Jurisprudence, the appointment of an amil is carried out by the authority of the caliph/sultan (state). In this case, the amil's position is as a representative of the zakat mustahik. It is important to note that the appointment of an amil should be approved by the state to ensure compliance with Islamic Jurisprudence. This research aims to address three problems related to the establishment and management of zakat at the mosque level in the city of Medan, according to Law No. 23/2011. Specifically, the research will examine: 1) the procedure for establishing zakat amil at the mosque level, 2) the management of zakat by the zakat amil at the mosque level, and 3) ways to optimise the management of zakat by the zakat amil at the mosque level. The language used is clear, objective and value-free, with a formal register and precise word choice. The text follows conventional structure and format, with a consistent style of quoting and footnoting. The sentences and paragraphs create a logical flow of information with causal links between propositions. The content has not been changed. This research has identified three key findings in this area. Firstly, the procedure for establishing Amil Zakat at the mosque level in the city of Medan is based on the policy of each mosque administrator (BKM). Secondly, the BKM's policy is then confirmed (validated) through the UPZ system by the National Amil Zakat Agency (BAZNAS) of the city of Medan. Finally, it is recommended that a more standardised procedure be implemented to ensure consistency across all mosques in the city. Zakat administration at the mosque level in the city of Medan is an ancillary activity that takes place only during the month of Ramadan and mainly within the framework of Zakat fitrah. During the collection phase, Amil opens a zakat booth at the mosque or at the BKM office, and potential muzakis come to the mosque to pay their zakat. Mosque Zakat Amil uses two methods: the coupon method and the delivery method for the distribution stage to the mustahik. Under the voucher system, a Muslim must present a voucher at the mosque in order to collect his zakat. Currently, the optimisation of zakat management in mosque zakat amil is limited to the collection and distribution stages, without taking into account the utilisation of zakat. Optimising Zakat collection is achieved through Zakat education, specifically by choosing recitation or lecture topics that focus on Zakat and by starting the Zakat collection period at the beginning of the month. During the distribution stage, optimization is achieved by prioritising mustahik selection, with a focus on actual mustahik. This research has found that there is little coordination between the Zakat Amil of the mosque and the BAZNAS, as well as between the Zakat Amil of the other mosques. It is important to address this issue in order to improve the effectiveness of the Zakat distribution.